A Gas Chromatography-Mass Spectrometry Based Study on Urine Metabolomics in Rats Chronically Poisoned with Hydrogen Sulfide. (14th April 2015) - Deng, Mingjie; Zhang, Meiling; Sun, Fa; Ma, Jianshe; Hu, Lufeng; Yang, Xuezhi; Lin, Guanyang; Wang, Xianqin
Abstract : Gas chromatography-mass spectrometry (GS-MS) in combination with multivariate statistical analysis was applied to explore the metabolic variability in urine of chronically hydrogen sulfide- (H2 S-) poisoned rats relative to control ones. The changes in endogenous metabolites were studied by partial least squares-discriminate analysis (PLS-DA) and independent-samples t -test. The metabolic patterns of H2 S-poisoned group are separated from the control, suggesting that the metabolic profiles of H2 S-poisoned rats were markedly different from the controls. Moreover, compared to the control group, the level of alanine, d-ribose, tetradecanoic acid, L-aspartic acid, pentanedioic acid, cholesterol, acetate, and oleic acid in rat urine of the poisoning group decreased, while the level of glycine, d-mannose, arabinofuranose, and propanoic acid increased. These metabolites are related to amino acid metabolism as well as energy and lipid metabolism in vivo . Studying metabolomics using GC-MS allows for a comprehensive overview of the metabolism of the living body. This technique can be employed to decipher the mechanism of chronic H2 S poisoning, thus promoting the use of metabolomics in clinical toxicology.